A Study on Supply Chain Management System Using Blockchain and IoT Technology - Yan, Hai-Shui; Kim, Hyung-Ho; Yang, Jun-Won (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The Internet-of-Things (IoT) expanded rapidly, resulting in many services, software products, and electrical devices integrated with sensors. It is associated with protocols that are currently under development. Blockchain technology serves as the foundation for most IoT-based applications, and it must be adaptable and widely disseminated to guarantee their survival. Blockchain-based IoT has several limitations due to its resource-constrained nature, including security, scalability, traceability, efficiency, and network throughput. The suggested method in this paper is a Privacy-assisted Information Exchange Framework (P-IEF), an integrated security mechanism that detects suspicious activities in sensor nodes and locates them on a blacklist. This approach is a centered digital ledger procedure that ensures the privacy of all nodes and ensures that the data can be validated without modifying any node, and there is no need for a third party to secure data. The simulation analysis shows trust measures and open challenges, and research difficulties examined in IoT environments. The privacy-assisted information exchange framework has achieved a security ratio of 98.25 %, a scalability ratio of 97.15 %, traceability rate of 98.54%, efficiency rate of 99.01 %, and network throughput ratio of 97.19 % outperforms compared with other approaches.